2014
DOI: 10.1007/s10802-014-9881-x
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Autism Spectrum Disorder based on DSM-5 Criteria: Evidence from Clinician and Teacher Reporting

Abstract: In the absence of intellectual impairment autism spectrum disorder (ASD) is diagnosed both less and later in females. This study used clinician and teacher report to explore sex differences in the behavioural presentation of 69 girls and 69 boys all diagnosed with high-functioning ASD. Evidence from DSM-IV-TR and DSM-5 are presented. Sex differences in teacher concerns were also explored. While no sex differences were found in the broad social criteria presented in the DSM-IV-TR or DSM-5, numerous differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
264
2
5

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 285 publications
(289 citation statements)
references
References 24 publications
18
264
2
5
Order By: Relevance
“…27 The trend of lower sex/gender ratio and dissociation may mean that recent studies have been more successful in identifying higher-functioning females, who may have been missed previously, particularly in clinic-or schoolbased samplings that are susceptible to bias. care-giving 28 The reason why we found equivalent prevalence in both genders may be because of a large sample size used in the study. It is pertinent to note that majority of our subjects who met the diagnostic criteria of autism were mainly within the age of 11-15 years.…”
Section: Resultsmentioning
confidence: 67%
“…27 The trend of lower sex/gender ratio and dissociation may mean that recent studies have been more successful in identifying higher-functioning females, who may have been missed previously, particularly in clinic-or schoolbased samplings that are susceptible to bias. care-giving 28 The reason why we found equivalent prevalence in both genders may be because of a large sample size used in the study. It is pertinent to note that majority of our subjects who met the diagnostic criteria of autism were mainly within the age of 11-15 years.…”
Section: Resultsmentioning
confidence: 67%
“…Social anxiety and ASD also share many similar aspects of presentation, and it is suggested that some of the avoidance techniques used by autistic individuals to minimise social difficulties may be misinterpreted as demonstrations of social anxiety [68]. Anxiety problems are also more commonly found in females with and without ASD [82,83], although are still highly prevalent amongst males [84]. It has been suggested that anxiety disorders may 'mask' some ASD symptoms in women, as the anxiety may be the most pressing clinical concern and so underlying ASD difficulties remain unidentified [68,85].…”
Section: Anxietymentioning
confidence: 99%
“…Several theses have been advanced about why this is the case. See Attwood et al (2006), Attwood (2007), Lai et al (2011Lai et al ( , 2012Lai et al ( , 2015Lai et al ( , 2017, Head et al (2014), Hiller et al (2014), Lehnhardt et al (2016), Parish-Morris et al (2017). 39 For instance, engaging in eye contact is taught as a set of instructions: look at the forehead or nose of the person you are talking to, count to five, look away, count to five, return to look at forehead again, etc.…”
Section: Fakesmentioning
confidence: 99%